Registration of 'YZ01‐1413' Sugarcane. Issue 2 (27th April 2017) - Zhao, Peifang; Liu, Jiayong; Wu, Caiwen; Yang, Hongchang; Zhao, Jun; Chen, Xuekuan; Xia, Hongming; Zan, Fenggang; Li, Jun; Yang, Kun; Wu, Zhuandi; Li, Fuqin; et al.
Abstract : 'YZ01‐1413' (Reg. No. CV‐170; PI 678580) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by Yunnan Sugarcane Research Institute (YSRI), of Yunnan Academy of Agricultural Sciences, and Yunnan Yunzhe Technology Development Co., Ltd. It was released to growers in Yunnan Province, China, on 9 June 2014. YZ01‐1413 was selected from the cross 'Yuetang 85‐177' × 'ROC10' planned by YSRI and crossed at the Yacheng Sugarcane Breeding Station of Guangzhou Sugar Industry Research Institute, Yacheng, Hainan Province of mainland China in December 2000. The female parent (Yuetang 85‐177) is a cultivar developed by the Guangzhou Sugar Industry Research Institute. The male parent (ROC10) is a cultivar developed by the Taiwan Sugar Research Institute. YZ01‐1413 was selected from a five‐stage selection program in YSRI and tested in the 11th Yunnan Regional Trial of Sugarcane Varieties at five locations of Yunnan Province for 2 yr. YZ01‐1413 was released by the Yunnan Committee of Crop Variety Release because of its higher cane yield compared with reference cultivars ROC10 and ROC22 (25.8 and 8.4%, respectively), higher sugar yield compared with ROC10 and ROC22 (25.5 and 7.4%, respectively), tolerance to drought, and high resistance to smut.